Personal Experiences and Expectations about Aggregate Outcomes - Theresa Kuchler; Basit Zafar (Institute for the Study of Labor (IZA), 2015)
We use novel survey data to estimate how personal experiences affect household expectations about aggregate economic outcomes in housing and labor markets. We exploit variation in locally experienced house prices to show that individuals systematically extrapolate from recent locally experienced home prices when asked for their expectations about US house price changes over the next year. In addition, higher volatility of locally experienced house prices causes respondents to report a wider distribution over expected future national house price movements. We find similar results for labor market expectations, where we exploit within-individual variation in labor market status to estimate the effect of own experience on national labor market expectations. Personally experiencing unemployment leads respondents to be significantly more pessimistic about future nationwide unemployment. The extent of extrapolation is unrelated to proxies for how informative personal experiences are, and is more pronounced for less sophisticated individuals.
Keywords: D83; D84; 330; expectations; experiences